Molecular Detection of Candida Qlabrata Isolated from Denture Stomatitis Patients - Haifa Abdul Ghani Abdulla; Eman A. Mustafa (University of Mosul, College of Dentistry, 2020)
Aims: This study aimed to detect and identify Candida glabrata isolated from denture stomatitis patients by using polymerase chain reaction( PCR). Materials and Methodes :Total of forty three of oral swabs samples were obtained from patients suffering from denture stomatitis attending prosthodontic departmentCollege of Dentistry /Mosul university/ Dental teaching Hospital. Clinically ,62 isolates of Candida spp. were identified to species level by standard culture methods using Sabouraud Dextrose agar(SDA) , HiCrome™ Candida Differential Agar followed by microscopic examination, and germ tube test. DNA extraction of Candida glabrata from broth cultures was carried out ,then molecular identification with PCR using specific primers targeting phospholipase B gene (PLB) were done to confirm C. glabrata diagnosis. Results: Among 62 isolates of Candida species , the predominant type was the Candida albicans which accounted for 29(46.8%) followed by Candida glabrata 21(33.9%), Candida tropicalis 11(17.7%), finally Candida krusei accounted for only 1 (1.6%) . HiCrome™ Candida Differential Agar do not easily recognize Candida spp. Sometimes C. glabrata was falsely identified as C. parapsilosis on HiCrome™ Candida Differential Agar. The result showed that the PCR products for the specific primer gave bands on agarose gel at the position 404 bp .Conclusion : Candida glabrata is emerging as the second most spreading among the isolates. Detection of PLB gene using PCR provides a definitive target that could be used for the identification and detection of Candida glabrata. from clinical samples .